Broadband alternating current photovoltaic effect: An application for high-performance sensing and imaging body aches. (November 2020) - Kumar, Mohit; Choi, Hyobin; Lim, Jaeseong; Park, Ji-Yong; Kim, Sangwan; Seo, Hyungtak
Abstract: Optoelectronic devices that can remotely sense discomfort or damage inside the human body are needed to improve the quality of human life. Herein, we report on the effective utilization of the alternating current photovoltaic effect to design self-powered, broadband photodetector with high detectivity (≈10 11 Jones) and a rise/decay time of 80/120 μs. The underlying working mechanism is attributed to quasi-Fermi level splitting and realignment caused by inhomogeneous absorption-induced imbalanced carrier generation, as was confirmed using Kelvin probe force microscopy and electrostatic force microscopy measurements. More importantly, the device was used to design and demonstrate a proof-of-concept real-time ultrafast (~7 ms) system for sensing and imaging body aches. Our simple, energy-efficient, and effective approach to the fabrication of this system with novel functionality can be easily integrated into existing planar structures, and the system has potential for use in medical, optical communication, digital display, and sensing applications. Graphical abstract: Conceptually new self-powered, broadband alternating current photodetector with high detectivity (≈10 11 Jones) and rise/decay time of 80/120 μs has been demonstrated. The underlying working mechanism is attributed to the quasi-Fermi Level splitting and realignment. Importantly, our optoelectronic device can remotely sense discomfort or damage inside the human body within ~7 ms, providing advancement for human life. Image 1 Highlights: Self‐powered, photo‐triggered, broadband alternating current photovoltaic effect was developed. The device shows ultrafast rise/decay time of 80/120 μs. The underlying working mechanism is attributed to the quasi-Fermi Level splitting and realignment. A proof-of-concept real-time ultrafast (~7 ms) system for sensing and imaging body aches has been demonstrated.